Tense and Aspect in Lohorung: A Functional-Typological Perspective - Rai, Tara Mani; Rai, Diwas (DMC Journal, 2025)
This study examines tense and aspect in Lohorung, a Rai Kirati language belonging to the Tibeto-Burman language family, from a functional typological perspective. The analysis is based on a corpus of naturally occurring texts and elicitation collected from native Lohorung speakers. These data are analyzed to identify how tense and aspect are structurally and functionally realized in the language. The findings indicate that tense and aspect in Lohorung are primarily expressed through morphological marking. At the same time, they exhibit systematic syntactic and semantic contrasts. The realization of tense and aspect morphemes varies according to syntactic environments. Similar marking strategies are attested in neighboring Kirati languages. The study further demonstrates that the tense system in Lohorung is organized around a binary distinction between past and non-past categories. Past tense is marked by the morpheme , whereas nonpast, or present, tense is marked by . The aspectual system is morphologically rich and includes multiple markers: perfective for completed actions, progressive for ongoing events, durative for extended actions, perfect for actions with present relevance, completive for brought-to-completion events, and habitual for repeated or customary actions.